2007
DOI: 10.2138/am.2007.2273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dioctahedral smectite hydration properties by modeling of X-ray diffraction profiles: Influence of layer charge and charge location

Abstract: SbId-1 and SbCa-1, respectively) was studied by modeling of X-ray diffraction patterns recorded under controlled relative humidity (RH) for Sr-and/or Ca-saturated specimens. The influence of layer charge and charge location on smectite hydration was studied. Distribution of layers with different hydration states (dehydrated -0W, monohydrated -1W, bi-hydrated -2W, or tri-hydrated -3W) within smectite crystals often leads to two distinct contributions to the X-ray diffraction pattern, each contribution having di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
148
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 42 publications
(31 reference statements)
19
148
0
Order By: Relevance
“…Even synthetic layered silicates when synthesized at temperatures below 1000 K show a non-uniform intracrystalline reactivity. As a consequence, a large fraction of the stacks does not show osmotic swelling at all, or the separation between adjacent layers varies randomly and a weighted average of the d-spacings is observed which is of limited analytical and practical value (16). Moreover, all the above mentioned materials need to be ion-exchanged and/or purified in some way prior to osmotic swelling.…”
Section: Resultsmentioning
confidence: 99%
“…Even synthetic layered silicates when synthesized at temperatures below 1000 K show a non-uniform intracrystalline reactivity. As a consequence, a large fraction of the stacks does not show osmotic swelling at all, or the separation between adjacent layers varies randomly and a weighted average of the d-spacings is observed which is of limited analytical and practical value (16). Moreover, all the above mentioned materials need to be ion-exchanged and/or purified in some way prior to osmotic swelling.…”
Section: Resultsmentioning
confidence: 99%
“…Using a systematic fitting procedure the evolution of layer type abundance and of crystal parameters can be followed accurately along the water vapor desorption isotherm, which allows assessing the specificity of the studied saponite by comparison with previous studies performed on natural smectites. 20,25,26 Structure Models and Crystal Parameters EWolution. The CSDSs along the c* axis (N parameter, Tables 1 and 2) are higher for saponites than for natural smectites.…”
Section: Discussionmentioning
confidence: 99%
“…A similar CSDS increase with decreasing hydration was already observed as a result of either RH decrease or temperature increase. 20,25,26 It was interpreted as a disruption of some 2W layer stacks owing to weaker electrostatic interactions between layers resulting from increasing interlayer distances upon hydration. Although consistent with this interpretation, the CSDS increase during the 2W-1W transition is less significant than that for Na-saturated low-charge montmorillonite (increase of ∼25% and ∼50%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sydration behavior of original montmorillonite has been extensively studied in past two decades [25][26][27][28][29], less attention has been paid to the structural characteristics of wet OMt [30][31][32]. Several previous reports indicated that X-ray diffraction (XRD) is still the most widely used method for characterizing the structure of OMt in water, and the results showed that water molecules can always cause evident swelling of OMt [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%